Formulation and Evaluation of Itraconazole Emulgel for Various Fungal Infections (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: In the past few decades, there has been an exponential growth in the field of herbal medicine andexcipients. The aim of the present research work was to investigate the potential of emulgel in enhancing thetopical delivery of itraconazole using natural gelling agents. Materials and Methods: Emulgel formulationsof itraconazole were formulated using two types of gelling agents, namely xanthan gum and guar gum. Theinfluence of the type of the gelling agent and the concentration of both the oil phase and emulsifying agent on thedrug release from the formulated emulgel was studied by preparing various batches. The prepared formulationswere evaluated for their physical appearance, viscosity, drug release, globule size, skin irritation test, antifungalactivity, and stability. Itraconazole cream available in market was used for comparison with prepared formulations.Results and Discussion: All the prepared emulgels showed acceptable physical properties concerning color,homogeneity, consistency, spreadability, and pH value. The result of studied revealed that the optimized batchshows 96.04% release in 5 h.